2020
DOI: 10.1002/rth2.12435
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular thrombus and pulmonary embolism: A case series of thrombosis in COVID‐19 in Thai patients

Abstract: Essentials • We present the first reported case of left ventricular thrombus in coronavirus disease 2019 (COVID-19). • Three consecutive cases of pulmonary embolism in Thai patients with COVID-19 are also demonstrated. • d-dimer is a strong marker to predict thrombosis. • Thromboprophylaxis is essential in Asian patients hospitalized with COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
(52 reference statements)
0
3
0
Order By: Relevance
“… 2 However, the specific mechanism of LV thrombus formation in COVID-19 is not well defined, 10 but is believed to be due to the hypercoagulability and local myocardial inflammation leading to the presence of relatively static blood resulting in thrombus formation. 11 The Virchow’s triad consisting of 3 major contributors to clot formation; namely, endothelial injury, stasis, and hypercoagulable state; applies to severe COVID-19 infection. Multiple processes 12 have been cited as the mechanism for the hypercoagulability in patients affected by SARS-CoV-2 and may include Direct infection of type II pneumocytes and endothelial cells increasing permeability.…”
Section: Discussionmentioning
confidence: 99%
“… 2 However, the specific mechanism of LV thrombus formation in COVID-19 is not well defined, 10 but is believed to be due to the hypercoagulability and local myocardial inflammation leading to the presence of relatively static blood resulting in thrombus formation. 11 The Virchow’s triad consisting of 3 major contributors to clot formation; namely, endothelial injury, stasis, and hypercoagulable state; applies to severe COVID-19 infection. Multiple processes 12 have been cited as the mechanism for the hypercoagulability in patients affected by SARS-CoV-2 and may include Direct infection of type II pneumocytes and endothelial cells increasing permeability.…”
Section: Discussionmentioning
confidence: 99%
“…To date, LV thrombosis in COVID-19 patients was associated with acute MI [ 90 , 91 , 92 ] and established cardiac disease [ 93 , 94 , 95 ], but also with the absence of any cardiac history both in young patients [ 96 , 97 ] and in elderly patients [ 98 ]. One study reported that among 368 patients admitted with COVID-19 and assessed by TTE during hospitalization, 4 had LV thrombus [ 99 ].…”
Section: The Use Of Doacs In Patients With LV Thrombusmentioning
confidence: 99%
“…To our knowledge, only a handful of cases resulting in ventricular thrombi caused by COVID-19 have been published. 1 , 2 , 3 , 4 , 5 , 6 , 7 All of the published cases were of relatively older patients (>40 years old). Additionally, another less common cardiovascular complication, with the most recent studies calculating an incidence of about 33%, 8 is COVID-related myocarditis.…”
Section: Introductionmentioning
confidence: 99%